Osteohistological insight into the early stages of growth in Mussaurus patagonicus (Dinosauria, Sauropodomorpha) - Cerda, Ignacio Alejandro (2014)
Here, we describe the bone histology of juvenile specimens of the basal sauropodomorph Mussaurus patagonicus and interpret its significance in terms of the early growth dynamics of this taxon. Thin sections from three juvenile specimens (femur length, 111-120 mm) of Mussaurus were analysed. The sampled bones consist of multiple postcranial elements collected from the Late Triassic Laguna Colorada Formation (El Tranquilo Group, Patagonia). The cortical bone is composed of fibrolamellar bone tissue. Vascularisation is commonly laminar or plexiform in the long bones. Growth marks are absent in all the examined samples. The epiphyses of long bones are all formed by well-developed hypertrophied calcified cartilage. The predominance of woven-fibred bone matrix in cortical bones indicates a fast growth rate in the individuals examined. Moreover, given the existence of growth marks in adult specimens of Mussaurus, as in other sauropodomorphs, and assuming that the first lines of arrested growth was formed during the first year of life, the absence of growth marks in all the bones suggest that the specimens died before reaching their first year of life. Compared with the African taxon Massospondylus carinatus (another basal sauropodomorph for which the bone histology has been previously studied), it appears that Mussaurus had a higher early growth rate than Massospondylus.